Occurrence of intraocular and orbital diseases in dogs: A retrospective study - NIRANJANA, C; SHAFIUZAMA, MOHAMED; RAMANI, C (The Indian Journal of Animal Sciences, 2023)
A total of 14,747 dogs were presented to Small Animal Ophthalmology unit of Madras Veterinary College Teaching Hospital for different ophthalmic diseases during the period of 2018 to 2021. Out of which, 649 (4.4%) dogs had less common intraocular and orbital diseases. The remaining 14,098 (95.6%) dogs had only corneal and extraocular diseases which were not included in this incidence study. The incidence was higher with cataract (n=170, 26.19%), followed by retinal detachment (n=96, 14.79%), proptosis (n=95, 14.64%) and retinal degeneration (n=89, 13.71%). Apart from these, incidence of eyeball lesions like exophthalmos was 2.16% (n=14), enophthalmos 0.46% (n=3) and anophthalmia 0.46% (n=3). The incidence of amaurosis was 7.86% (n=51), hyphema 5.39% (n=35), lens luxation 3.08% (n=20), glaucoma 2.31% (n=15) and panophthalmitis 6.78% (n=44). Incidence of intraocular tumours 1.23% (n=8) and retrobulbar tumours was 0.92% (n=6).